FAKTOR YANG MEMPENGARUHI CITRA MEREK SPEEDY PADA PT. TELKOM RIAU DARATAN PEKANBARU - Rini Elawani; Numan M.Si (UIR Press, 2015)
The rapid development period followed by increased globalization in the field ofinformation technology, whe information can be identified quickly, so those who want toevolve constantly follow the development of these technologies because oftheirknowledge and use of technology is a demand of the times.One of the technologies ofinformation is the Internet. Therefore, to satisfy customers PT. Telkom Riau Pekanbaruissued aproduct named Speedy. The purpose of this study is to know and explain aboutthe factor which influence the brand image speedy. The population in this study is thecustomer that use the speedy product from PT. Telkom Riau Daratan Pekanbaru. Thesample of this study are 50 costumers of speedy’s product taken by using insidentalsampling that determination techniques sample based on the coincidence. The authorgives a questionnaire to customers who happen to pay a speedy betwen 1 to 15 duringhours working. The data collection is done by using quistionaire and interview. Dataprocessed using quantitative methods. The results of data processing show that of thethree factors studied was a faktor excellence become the dominant brand associationdetermine the use speedy. Because there are two factors that are not yet using speedythat determining the strength of brand association and uniqueness of brand association,thus the authors suggest that PT. Telkom Riau Daratan Pekanbaru further enhance thestrength and uniqueness of brand association speedy such as promotion is furtherenchanced, made attractive brand design and brand colors brightened too make it lookmore clerly.